2012
DOI: 10.1007/s12192-011-0314-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased immunogenicity is an integral part of the heat shock response following renal ischemia

Abstract: Renal ischemia increases tubular immunogenicity predisposing to increased risk of kidney allograft rejection. Ischemia-reperfusion not only disrupts cellular homeostasis but also induces the cytoprotective heat shock response that also plays a major role in cellular immune and defense processes. This study therefore tested the hypothesis that upregulation of renal tubular immunogenicity is an integral part of the heat shock response after renal ischemia. Expressions of 70 kDa heat shock protein (Hsp70), major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Nevertheless, we show that loss of biglycan leads to reduction of HSP70 expression, which is associated with a decreased pro-inflammatory signaling and a less severe inflammation. Several studies have shown that pharmacological HSP70 induction protects renal tissue from IRI damage [81][82][83]. Our data suggest that in ROS-mediated renal inflammation targeting biglycan and consequently inhibiting HSP70 expression might limit renal pathology.…”
Section: Ros-dependent Nlrp3 Inflammasome Activationmentioning
confidence: 56%
“…Nevertheless, we show that loss of biglycan leads to reduction of HSP70 expression, which is associated with a decreased pro-inflammatory signaling and a less severe inflammation. Several studies have shown that pharmacological HSP70 induction protects renal tissue from IRI damage [81][82][83]. Our data suggest that in ROS-mediated renal inflammation targeting biglycan and consequently inhibiting HSP70 expression might limit renal pathology.…”
Section: Ros-dependent Nlrp3 Inflammasome Activationmentioning
confidence: 56%
“…Class Ia DAMPs such as HMGB1 and HSPs are generated in reperfusion‐injured organs including human renal allografts , but also emitted under BD conditions . These molecules considerably contribute to creation of sterile inflammation including IRI‐mediated inflammation when sensed by those members of the NLR or ALR family that form inflammasomes .…”
Section: A Plethora Of Damps and An Attempt To Classify Themmentioning
confidence: 99%
“…Small children receiving adult size kidneys are at increased risk of DGF and thrombosis, possibly as a result of their low cardiac output in relation to the transplanted organ [4,5]. Ischaemia‐reperfusion injury is involved in the development of DGF and cellular lesions play a role in up‐regulating the expression of class II MHC [6,7].…”
Section: Introductionmentioning
confidence: 99%